Dexmedetomidine to reduce vasopressor resistance in refractory septic shock: Protocol for a double-blind randomized controlled pilot trial (ADRESS Pilot study) - Dargent, Auguste; Bourredjem, Abderrahmane; Argaud, Laurent; Levy, Bruno; Fournel, Isabelle; Cransac, Amélie; Badie, Julio; Quintin, Luc; Quenot, Jean-Pierre (Frontiers in Medicine, 2022)
Introduction Refractory septic shock (RSS) is associated with high mortality. It is characterised by high vasopressor requirements, as a consequence of vasopressor resistance, which may be caused or enhanced by the sympathetic hyperactivation observed in RSS. Accordingly, sympathetic deactivation with alpha-2 agonists in patients with shock reduces vasopressor requirements. Experimental models support the efficacy of dexmedetomidine during septic shock, showing a reduction in vasopressor requirements and improved microcirculation compared to conventional sedation. Dexmedetomidine did not reduce mortality in clinical trials, but few septic shock patients were enrolled. This pilot trial aims to evaluate vasopressor re-sensitization with dexmedetomidine and assess the effect size, in order to design a larger trial. Methods This is an investigator-initiated, multicentre, randomised, double-blind, placebo-controlled trial, comparing dexmedetomidine versus placebo in RSS patients with norepinephrine dose ≥0.5µg/kg/min. The primary outcome is blood pressure response to phenylephrine challenge, 6 hours after completion of a first challenge, after study treatment initiation. The sample size is estimated at 32 patients. Secondary outcomes include mortality, vasopressor requirements, heart rate variability, plasma and urine catecholamines levels. Blood pressure and ECG will be continuously recorded for the first 24 hours, enabling high-quality data collection for the primary and secondary endpoints. The study was approved by the ethics committee “Sud-Est VI” (2019-000726-22) and patients will be included after informed consent. Discussion The present study will be the first randomised trial to specifically address the hemodynamic effects of dexmedetomidine in patients with septic shock. We implemented a high-quality process for data acquisition and recording in the first 24 hours, allowing maximal quality for the evaluation of both efficacy and safety outcomes, as well as transparency of results. The results of the study will be used to elaborate a full-scale randomised controlled trial with mortality as primary outcome in RSS patients. Trial registration: Registered with ClinicalTrials.gov (NCT03953677). Registered 16 May 2019, https://clinicaltrials.gov/ct2/show/NCT03953677